Best Practice Guidelines for Hip Arthroscopy in Femoroacetabular Impingement: Results of a Delphi Process. Issue 2 (15th January 2020) - Lynch, T. Sean; Minkara, Anas; Aoki, Stephen; Bedi, Asheesh; Bharam, Srino; Clohisy, John; Harris, Joshua; Larson, Christopher; Nepple, Jeffrey; Nho, Shane; Philippon, Marc; Rosneck, James; et al.
Abstract : Background: Treatment algorithms for the arthroscopic management of femoroacetabular impingement (FAI) syndrome remain controversial because of a paucity of evidence-based guidance. Consequently, notable variability in clinical practice exists between different practitioners, necessitating expert consensus. The purpose of this study is to establish best practice guidelines (BPG) using formal techniques of consensus building among a group of experienced hip arthroscopists driven by the results of a systematic review and meta-analysis. The scope of these guidelines includes preoperative recommendations, intraoperative practices, and postoperative protocols. Methods: The validated Delphi process and the nominal group technique (NGT), used by the Centers for Disease Control and Prevention and the peer-reviewed orthopaedic literature, were used to formally derive consensus among 15 surgeons in North America. Participants were surveyed for current practices, presented with the results of a meta-analysis and systematic literature review, and asked to vote for or against the inclusion of nonleading, impartially phrased items during three iterative rounds while preserving the anonymity of participants' opinions. Agreement greater than 80% was considered consensus, and items near consensus (70% to 80% agreement) were further queried using the NGT in a moderated group session at the American Orthopaedic Society for Sports Medicine annual meeting. Results: Participants had a mean of 12.3 years of practice (range: 1 to 29 years) and performed an annual mean of 249 (range 100 to 500+) hip arthroscopies, with a combined total of approximately 52, 580 procedures. Consensus was reached for the creation of BPG consisting of 27 preoperative recommendations, 15 intraoperative practices, and 10 postoperative protocols. The final checklist was supported by 100% of participants. Conclusion: We developed the first national consensus-based BPG for the surgical and nonsurgical management of FAI. The resulting consensus items can serve as a tool to reduce the variability in preoperative, intraoperative, and postoperative practices and guide further research for the arthroscopic management of FAI.